A Study Bukit Siguntang as the Sacred Heritage of the Ancestral Land of the Malay Nation: From Profane to Sacred - ming, david (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
Bukit Siguntang is an important piece of evidence of the historical heritage of the Srivijaya Kingdom in Palembang. It is estimated to have originated in the 6th century AD. Although the system of Palembang society has changed from Buddhist society to Islamic society since the development of the Palembang Sultanate, the heritage is still considered sacred by the Malay community around the site so that the existence of the historical site is preserved. However, the condition of the site is not maintained according to its function now. This study aimed to analyse changes in the meaning of the site by the community and government and its impact on the site damage. This study used a qualitative method with a historical approach. The results of the study showed that there was a change in the meaning of the Bukit Siguntang site between the government and the community, so that there was a struggle for space utilization between the government and groups of activists to rescue the historical heritage. The local government interpreted the site as a tourism asset that had to be